Serum free immunoglobulin light chain fingerprint identifies a subset of newly diagnosed multiple myeloma patients with worse outcome - Avivi, I.; Cohen, Y.C.; Joffe, E.; Benyamini, N.; Held-Kuznetsov, V.; Trestman, S.; Terpos, E.; Dimopoulos, M.A.; Kastritis, E. (Hematological Oncology, 2016)
Multiple myeloma (MM) is a multi-subclonal malignancy with relatively high heterogeneity. Patients who initially presented with both monoclonal-protein (MP) and free light chain (FLC) secretion but then relapsed with a light chain escape pattern have been shown to reflect disease clonal evolution and to bare a worse prognosis. We hypothesized that a discordant MP/FLC pattern at diagnosis may reflect a similar clonal evolution that had occurred prior to diagnosis of active myeloma, conferring a worse outcome. We analyzed 255 consecutive newly diagnosed MM patients who received first line bortezomib-based therapy between 2007 and 2014, hypothesizing that their MP/FLC fingerprint at diagnosis reflects clonal heterogeneity and, therefore, affects outcome. An involved FLC level ≥ 700 mg/L and MP ≥ 2.5 g/L were used as cutoffs for low vs high FLC and MP levels, respectively. Patients were divided into 4 subgroups according to their involved FLC and MP blood levels at diagnosis: HiLC and HiMP for patients with either a predominant FLC or a predominant MP, respectively, and HiLC-MP and LoLC-MP when both FLC and MP were increased or decreased, respectively. There were 68 (27%) patients with HiLC, which presented more often with International Staging System-3 stage (P < .0001). Multivariate analysis showed that HiLC was associated with a 5.1-fold risk for mortality in a multivariate model (95% confidence interval [CI], 1.34-19.68). Both HiLC and HiLC-MP phenotypes were associated with shorter progression-free survival (hazard ratio of 2.66 [95% CI, 1.33-5.32] and 2.82 [95% CI, 1.37-5.83], respectively), independently of other prognostic factors, including the use of autograft. Thus, we identified an LC predominant secretory fingerprint (HiLC phenotype) at diagnosis as a potential independent risk factor that may affect disease control and survival in newly diagnosed MM patients treated with bortezomib-based induction therapy; this may represent increased subclonal heterogeneity. © 2016 John Wiley & Sons, Ltd.
Keywords: Light chain; myeloma; Prognosis; Secretory